Pemanfaatan Sampah Bernilai Ekonomis, Penyuluhan Pemanfaatan Sampah Menjadi Kompos Dengan Metode Takakura Di Desa Bale Kambang Kecamatan Mancak Kabupaten Serang - Ade Millatus Sa’adiyyah (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2019)
The aim of the Community Service Program Community Work and Community Empowerment Study Program (KKN-PPM) is to provide counseling to residents of Bale Kambang Village, Mancak District, Serang Regency. The problem faced in Bale Kambang Village is about rubbish, rubbish produced from households and plants around the house, ie the community does not know about processing to compost using the Takakura method so that it can ultimately increase community productivity and well-being that has value selling. The methods of implementing this service are (1) survey through initial observation, problem analysis, interviews, and documentation. (2) Counseling for composting using the Takakura method. This community service program is expected to provide additional knowledge to the community and to provide added value about composting using the Takakura method which is very simple and can have selling points to increase the welfare of the community, so that Bale Kambang Village in Mancak District can be made into a clean village and its people are clean. skilled and have high productivity.